The kidney and skin duo in SARS-CoV-2/COVID-19 (2021)
ABSTRACT: SARS-CoV-2 infection has spread to a huge number of countries. After viral exposure, 80% of the cases will behave as mild or asymptomatic, around 15% will require a hospital facility and 5% will require Intensive-Care-Unit (ICU) management and the use of mechanical ventilation. Although SARS-CoV-2 is not as lethal as other severe acute respiratory syndromes (SARS) viruses, it has caused more infections, deaths and economic impact than any other worldwide infectious disease. According to initial pandemic reports, acute kidney injury (AKI) has occurred in around 3-9% of COVID-19 patients, however, not only those numbers have increased up to 20-42% in critically ill cases and in deceased people, but also, patients with renal involvement seem to have an increased risk of mortality. Similarly, cutaneous manifestations in COVID-19 have presented in around 8-20% of patients and are also subtle at the beginning, but later on they can progress to more severe skin disease. Common COVID-19 pathogenic features seem to be shared by the kidney and the skin and such cutaneous manifestations might be an alert for the need of early kidney function monitoring in order to initiate supportive interventions that may protect such organ from severe renal dysfunction and end stage disease.